2017
DOI: 10.1136/bmjopen-2016-015123
|View full text |Cite
|
Sign up to set email alerts
|

Associations between highly active antiretroviral therapy and the presence of HPV, premalignant and malignant cervical lesions in sub-Saharan Africa, a systematic review: current evidence and directions for future research

Abstract: ObjectivesIn sub-Saharan Africa, substantial international funding along with evidence-based clinical practice have resulted in an unparalleled scale-up of access to antiretroviral treatment at a higher CD4 count. The role and timing of highly active antiretroviral therapy (HAART) in mediating cervical disease remains unclear. The aim of this article is to systematically review all evidence pertaining to Africa and identify research gaps regarding the epidemiological association between HAART use and the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 38 publications
1
38
0
Order By: Relevance
“…From our study, other categories, LSIL and HSIL were of lower prevalence compared to Dim et al, (2011) and reports from outside our study center on HIV+ve not on therapy, hence one can say that HAART reduces progression of cervical dysplasia among HIV+ve females, which is consistent with some previous reports (Minkoff et al, 2010;Alder et al, 2012;Firnhaber et al, 2012;Blitz et al, 2013;Ezechi et al, 2014;Katz et al, 2016). Firnhaber et al, (2012) concluded that HAART use reduced the rate of incidence and progression of cervical lesions among HIV+ve females and was dependent on duration of regimen but Menon et al, (2017), reported in their systematic review of effects of HAART on cervical dysplasia in sub Saharan Africa, suggested that CD4+ cell count may have a more instrumental role in cervical oncogenesis or the integration of the latent reservoir throughout the body than either HAART use or the treatment duration on the prevalence of CIN 2 and CIN 3. Minkoff et al, (2010) concluded that effective and adherent HAART use was associated with a significantly reduced burden of HPV infection and Squamous Intraepithelial Lesions (SILs).…”
Section: Discussionsupporting
confidence: 91%
“…From our study, other categories, LSIL and HSIL were of lower prevalence compared to Dim et al, (2011) and reports from outside our study center on HIV+ve not on therapy, hence one can say that HAART reduces progression of cervical dysplasia among HIV+ve females, which is consistent with some previous reports (Minkoff et al, 2010;Alder et al, 2012;Firnhaber et al, 2012;Blitz et al, 2013;Ezechi et al, 2014;Katz et al, 2016). Firnhaber et al, (2012) concluded that HAART use reduced the rate of incidence and progression of cervical lesions among HIV+ve females and was dependent on duration of regimen but Menon et al, (2017), reported in their systematic review of effects of HAART on cervical dysplasia in sub Saharan Africa, suggested that CD4+ cell count may have a more instrumental role in cervical oncogenesis or the integration of the latent reservoir throughout the body than either HAART use or the treatment duration on the prevalence of CIN 2 and CIN 3. Minkoff et al, (2010) concluded that effective and adherent HAART use was associated with a significantly reduced burden of HPV infection and Squamous Intraepithelial Lesions (SILs).…”
Section: Discussionsupporting
confidence: 91%
“…Three other studies of HIV-infected sub-Saharan women also indicate a positive impact of ART on reducing HR-HPV detection, as reviewed by Menon et al [30]. A meta-analysis also concluded that ART use, after adjusting for duration of use and CD4 count, was associated with reduced rate of HR-HPV in HIV-infected women [31].…”
Section: Discussionmentioning
confidence: 88%
“…8,9,16,213,214 Some evidence suggests that ART lowers the risk of persistent HPV infection and the prevalence of cervical intraepithelial neoplasia (CIN), precursors of cervical cancer. [215][216][217][218] However, evidence that the incidence of cervical cancer in WLWH has decreased significantly in the modern ART era is lacking. 8,10,12,17,127,219 In 2010, cervical cancer accounted for approximately 1% of cancers diagnosed in the HIV population.…”
Section: Cervical Cancer In Plwhmentioning
confidence: 99%